2012
DOI: 10.1371/journal.pone.0052406
|View full text |Cite
|
Sign up to set email alerts
|

Transforming Growth Factor-β, Macrophage Colony-Stimulating Factor and C-Reactive Protein Levels Correlate with CD14highCD16+ Monocyte Induction and Activation in Trauma Patients

Abstract: Severe injury remains a leading cause of death and morbidity in patients under 40, with the number of annual trauma-related deaths approaching 160,000 in the United States. Patients who survive the initial trauma and post-traumatic resuscitation are at risk for immune dysregulation, which contributes to late mortality and accounts for approximately 20% of deaths after traumatic injury. This post-traumatic immunosuppressed state has been attributed to over-expression of anti-inflammatory mediators in an effort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 35 publications
3
23
0
Order By: Relevance
“…CD32 also plays an essential role in the removal of antigen-antibody complexes from the circulation and cell-tocell interactions mediating antibody-dependent cell-mediated cytotoxicity. CD14 + CD16 + monocytes are reportedly increased in sepsis patients with severe infection [40] and efficiently produce the pro-inflammatory cytokine TNF-α, while they produce no or little of the anti-inflammatory cytokine IL-10 [41]. Our results also showed significantly up-regulated frequencies of CD14 + CD16 + subsets in BD patients (Figure 3) and markedly elevated IL-10 levels in improved inactive BD patients compared to active BD patients (Figure 6).…”
Section: Discussionsupporting
confidence: 60%
“…CD32 also plays an essential role in the removal of antigen-antibody complexes from the circulation and cell-tocell interactions mediating antibody-dependent cell-mediated cytotoxicity. CD14 + CD16 + monocytes are reportedly increased in sepsis patients with severe infection [40] and efficiently produce the pro-inflammatory cytokine TNF-α, while they produce no or little of the anti-inflammatory cytokine IL-10 [41]. Our results also showed significantly up-regulated frequencies of CD14 + CD16 + subsets in BD patients (Figure 3) and markedly elevated IL-10 levels in improved inactive BD patients compared to active BD patients (Figure 6).…”
Section: Discussionsupporting
confidence: 60%
“…Monocytes and macrophages are key initiators and regulators of innate immune responses following trauma. In a study of 50 trauma patients, we observed an increase in an activated monocyte/macrophage population (CD14 high CD16 + CD163 + ) in the blood that was highly correlated with CRP levels, as well as M-CSF and TGF- β [239], M-CSF and TGF- β found in trauma plasma could induce this phenotype in normal monocytes. Although it was not essential for inducing the phenotype, CRP activated M-CSF differentiated monocytes to produce anti-inflammatory cytokines, IL-10 and IL-1RA.…”
Section: Crp In Sepsis and Shockmentioning
confidence: 99%
“…Similar studies in obesity and trauma demonstrate that monocyte subsets have prognostic value with regards to disease severity and clinical outcomes 26, 27 . Importantly, in all of these diseases, our current understanding has progressed first from an appreciation that absolute monocyte levels are predictive, to a more nuanced appreciation that monocyte heterogeneity and ultimately the functional consequences of this heterogeneity contribute to disease pathogenesis.…”
Section: Discussionmentioning
confidence: 80%